A Cross-Sectional Multifactorial Analysis Of Chrononutrition, Sleep Quality And Sleep Patterns Among Healthcare Shift Workers - Emmanuel Ngelayang Franky Giltelin; Nur Islami Mohd Fahmi Teng; Nor Amira Syahira Mohd Azmi; Siti Nuramira Mohamed; Muhammad Husni Mulhim; Sofwatul Mokhtarah Maluin; Norsham Juliana Nordin (MDPI, 2026)
Indexed by WOS / SCOPUS / ERA